2018
DOI: 10.18488/journal.11.2018.74.204.214
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Organic Food Consumption from a Sustainability Perspective and Future Research Directions

Abstract: Article HistoryKeywords Organic food Historical evolution Sustainability movement Critical literature review Research gaps Future research directions.This paper reviews organic food consumption from a sustainability perspective with a view to suggesting future research directions. It gives an overview of historical evolution of organic food consumption as a sustainability movement and provides a critical review of a large body of previous research, which examines organic food consumption from various perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…According to [21], consumers' positive perceptions of organic food have increased owing to the quality of organic food being higher than that of non-organic products. Previous studies have reported that product-quality is one of the main antecedents for increasing organic food consumption [44]. An empirical study found that product quality was the most important motive for purchasing organic food among Indian consumers [11].…”
Section: B Food Qualitymentioning
confidence: 99%
“…According to [21], consumers' positive perceptions of organic food have increased owing to the quality of organic food being higher than that of non-organic products. Previous studies have reported that product-quality is one of the main antecedents for increasing organic food consumption [44]. An empirical study found that product quality was the most important motive for purchasing organic food among Indian consumers [11].…”
Section: B Food Qualitymentioning
confidence: 99%
“…On the other hand, the results of causal investigation suggested that environmental degradation and trade openness have a bi-directional causal association in the sampled countries. Furthermore, Li, Xu, &, Yuan, (2015); Perera, Johnson & Hewege (2018) also analyzed the relationship between trade liberalization and environment. The study utilized the panel data of 131 developed and developing countries from 1961 to 2004.…”
Section: Literature Reviewmentioning
confidence: 99%
“…UMK provides numerous projects, for example, the Students in Enterprise Program (SIEP) and the Social Entrepreneurship Program where the students will end up taking an interest in a program for economic and community advancement. This is directed through a social business enterprise subject (Al Mamun et al, 2016;Perera, Johnson & Hewege 2018). Hence, in conducting the research, Holland Test Occupational Theme was used to test the personality entrepreneurial students.…”
Section: Literature Reviewmentioning
confidence: 99%